Legal Analysis Of The Validity Of Siri Marriages According To Law Number 1 Of 1974 Concerning Marriage - Pujja Dwi Sartika; Ferawati Royani; Sandi Aprianto (JURNAL HUKUM SEHASEN, 2026)
Marriage is a legal event that gives rise to broad civil legal consequences, both for husband, wife, and children. In the Indonesian legal system, the validity of marriage is regulated by Law Number 1 of 1974 concerning Marriage, which requires the fulfillment of religious provisions and the obligation of registration by the state. However, in practice, many people still conduct unregistered marriages, namely marriages that are valid according to religious law but are not administratively registered. This phenomenon creates legal problems because it creates a dualism between religious validity and state legal legality. This study aims to analyze the legal provisions regarding the validity of marriage according to Law Number 1 of 1974 and examine the legal position of unregistered marriages from the perspective of positive law and other related laws and regulations. This study uses a normative legal research method with a statutory and conceptual approach, by examining primary, secondary, and tertiary legal materials. The research results show that unregistered marriages, although valid according to religion, lack legal force under positive law because they do not meet the formal requirements for registration as stipulated in Article 2 paragraph (2) of Law Number 1 of 1974. The legal consequences of unregistered marriages weaken legal protection for wives and children, particularly regarding the rights to maintenance, inheritance, child status, and joint property. The state provides a marriage confirmation mechanism as a repressive legal protection measure, but this mechanism is limited and is not intended to legalize unregistered marriages. Therefore, marriage registration is an important instrument in achieving legal certainty and protecting civil rights within the national marriage law system.